2023
DOI: 10.1038/s41698-023-00361-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ACE2-BRD4 crosstalk in colorectal cancer and the deregulation of DNA repair and apoptosis

Abstract: ACE2 overexpression in colorectal cancer patients might increase susceptibility to SARS-CoV-2 infection. We report that knockdown, forced overexpression, and pharmacologic inhibition in human colon cancer cells targeted ACE2-BRD4 crosstalk to mediate marked changes in DNA damage/repair and apoptosis. In colorectal cancer patients for whom high ACE2 plus high BRD4 expression is predictive of poor survival, pan-BET inhibition would need to consider proviral/antiviral actions of different BET proteins during SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This archetype is enriched for hallmarks of cell proliferation (Hallmark genesets G2M checkpoint, E2F targets) and growth (MYC Targets V1/2, mTORC1 signaling). The top markers of this cluster include CDC20, CDK1 and CDK4, key regulators of phase transitions during the cell cycle [47]. Concomitantly, analysis of cell cycle in the cells most strongly associated with this archetype revealed that >95% were in either the S or G2M phase (Supplementary Figure 5a-b).…”
Section: Resultsmentioning
confidence: 99%
“…This archetype is enriched for hallmarks of cell proliferation (Hallmark genesets G2M checkpoint, E2F targets) and growth (MYC Targets V1/2, mTORC1 signaling). The top markers of this cluster include CDC20, CDK1 and CDK4, key regulators of phase transitions during the cell cycle [47]. Concomitantly, analysis of cell cycle in the cells most strongly associated with this archetype revealed that >95% were in either the S or G2M phase (Supplementary Figure 5a-b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the main nodes mentioned, BUB1, CCND1, CDK1, and PCNA, other studies also show the importance of NOP58, EZH2 and PPPC1A in tumorigenesis [ 44 46 ]. All these genes are interconnected in a complex network that ensures the correct control of cell division and genomic stability, emphasizing CDK1, as master regulator [ 39 ]. CDK1, CCND1, and PCNA play distinct roles in different phases of cell cycle and have been identified as pivotal genes in the development and progression of different cancer types, including colon, liver, and gynecological tumors [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 The protein complex encoded by this gene participates in the cell cycle process by regulating cell cycle factors, causing cell cycle disruption, and directly contributing to cancer cell proliferation and growth. 37 Kinesin Family Member 4A (KIF4A) encodes a member of the kinesin-4 subfamily of motor proteins. The encoded protein is an ATP-dependent microtubule motor protein involved in intracellular transport of membranous organelles.…”
Section: Discussionmentioning
confidence: 99%